"Look at Me! I Can Change Your Tire": Queer Female Masculinity in the Gym. (1st September 2021) - Newhall, Kristine
Abstract: Outside of bodybuilding, queer women in fitness and exercise cultures have received little attention in popular discourse and academic research. In this article, I examine how queer use of gym space can inform and reify a queer identity, specifically the enactment of queer female masculinity. I use Jack Halberstam's work on female masculinity and literature in the fields of cultural studies and sport studies to discuss how queer identity, space, and power operate on the body in the context of fitness culture.